SHEAR RESISTENCE REGULARITIES OF SUBSIDENT SOILS UNDER SOAKING OVER A WIDE RANGE OF ALTERATIONS OF COMPACTING STRESSES (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
Strength behavior of water saturated subsidented soils is studied. A linear dependence of relative subsidence deformation of compacting stresses while σzPsl,0  is found out  experimentally. In conditions of water saturation the shear resistance chart represents a broken line, which vertex corresponds to the initial subsidence value. Necessity to determine the shear resistance arguments for each compacting stress σz>Psl,0 on reverse branch of compression curves on Nichiporovich method is established.
Keywords: saturated subsidented soils; shear; shear resistance